2011
DOI: 10.1016/j.nuclphysa.2010.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Microscopically-constrained Fock energy density functionals from chiral effective field theory. I. Two-nucleon interactions

Abstract: The density matrix expansion (DME) of Negele and Vautherin is a convenient tool to map finiterange physics associated with vacuum two-and three-nucleon interactions into the form of a Skymelike energy density functional (EDF) with density-dependent couplings. In this work, we apply the improved formulation of the DME proposed recently in arXiv:0910.4979 by Gebremariam et al. to the non-local Fock energy obtained from chiral effective field theory (EFT) two-nucleon (NN) interactions at next-to-next-to-leading-o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 65 publications
(114 reference statements)
0
44
0
Order By: Relevance
“…Only very recently this route was started to be explored in non-relativistic EDFs, see, Refs. [83][84][85][86][87][88][89][90][91], so its eventual impact on the physics discussed here is not yet known. …”
Section: Discussionmentioning
confidence: 99%
“…Only very recently this route was started to be explored in non-relativistic EDFs, see, Refs. [83][84][85][86][87][88][89][90][91], so its eventual impact on the physics discussed here is not yet known. …”
Section: Discussionmentioning
confidence: 99%
“…In this section we review how chiral low-momentum interactions can be employed for the description of properties of finite nuclei [85,86,87,88,89,90]. We leave aside the highly sophisticated ab-initio methods which have been developed over the past decades in order to solve (numerically) the nuclear A-body problem with a given two-and three-nucleon interaction.…”
Section: Density Functional Methods and Finite Nucleimentioning
confidence: 99%
“…[86]. There it has been suggested that the density-dependent couplings associated with pion-exchange should be added to a standard Skyrme functional with re-adjusted parameters.…”
Section: Density Functional Methods and Finite Nucleimentioning
confidence: 99%
“…Extensions of the first calculations from [11] have modified the original DME formalism from Negele and Vautherin [21,22], whose deficiencies include an extremely poor description of the vector part of the density matrix. Gebremariam and collaborators [26,27] introduced a new phase-space-averaging (PSA) approach. The PSA approach leads to substantial improvements, particularly for the vector density, where relative errors in integrated quantities are reduced by as much as an order of magnitude across isotope chains.…”
Section: A Dmementioning
confidence: 99%